Reformulating Islamic Epistemology: Solution to The Crisis of Modern Science, Technology and The Impact of Globalization - Muh. Yusuf Kasim (Ar-Raniry: International Journal of Islamic Studies, 2021)
The progress of science, technology, and globalization has had such a huge impact on human civilization, both positive and negative impacts. This research studies the various impacts and offers epistemology which is based on the foundation of Divine transcendental values that refer to the framework of the Qur'an and Sunnah. This is intended to save humans from their fall as spiritual beings. To realize this, the axillogical, ontological, and epistemological aspects need to be reformulated based on the Qur'an and Sunnah. In exploring these instructions, a semantic approach is needed as an internal analysis of the text. Whereas the contextual approach requires tracking the historical context that 'forms the text', namely micro and macro socio-historical to be drawn into the context of reality that continues to change without limits. Thus a limited sacred text will always be able to dialogue with unlimited context changes. The epistemological framework built from it is expected to be able to inspire the progress of human civilization universally. Institutional transformation from STAIN to IAIN and from IAIN to UIN by developing a paradigm of integration of Islam and sciences. As an effort, consistency, revitalization and sustainability are needed to achieve the glory of universal Islamic civilization.